Elevated EMMPRIN Serum Levels Indicate Plaque Vulnerability in Patients With Asymptomatic High Grade Carotid Stenosis. (April 2023) - Kampf, Stephanie; Micko, Alexander; Stojkovic, Stefan; Nackenhorst, Maja; Demyanets, Svitlana; Eilenberg, Wolf-Hans; Krenn, Claus; Wojta, Johann; Neumayer, Christoph
Abstract : Objective: Carotid atherosclerosis is an important cause of cerebral ischaemic stroke. Sonographic plaque characteristics are inappropriate for exact prediction of possible future ischaemic events. Additional markers are needed to predict the clinical outcome in high grade carotid stenosis. This study aimed to test extracellular matrix metalloproteinase inducer (EMMPRIN), due to its involvement in plaque formation and destabilisation, as a potential marker of high risk vulnerable plaques. Methods: EMMPRIN was analysed in pre-operative serum samples from patients with symptomatic and asymptomatic carotid artery stenosis by a specific ELISA. Pre-operative duplex sonography classified the atherosclerotic plaque due to echogenicity. Histopathological analysis of vulnerable and non-vulnerable plaques was based on the American Heart Association (AHA) classification. Results: The study included 265 patients undergoing carotid endarterectomy: 90 (m:f, 69:21) patients with symptomatic and 175 (m:f, 118:57) with asymptomatic disease. Analysis of circulating EMMPRIN revealed significantly higher levels in patients with echolucent plaques (4 480; IQR 3 745, 6 144 pg/mL) compared with echogenic plaques (4 159; IQR 3 418, 5 402 pg/mL; p  = .025). Asymptomatic patients with vulnerable plaques had significantly higher levels of EMMPRIN (4 875; IQR 3 850, 7 016 pg/mL) compared with non-vulnerable plaques (4 109; IQR 3 433, 5 402 pg/mL; p < .001). In logistic regression analysis, duplex sonography combined with age, gender, and clinical risk factors predicted vulnerable plaques in asymptomatic patients with an AUC of 0.71 (95% CI 0.61 – 0.80). EMMPRIN significantly improved the AUC in asymptomatic patients (AUC 0.79; 95% CI 0.71 – 0.87; p  = .014). Conclusion: Patients with high risk plaques according to ultrasound and histopathological characteristics demonstrated increased serum EMMPRIN levels. EMMPRIN on top of clinical risk factors, including age, gender, and duplex sonography may be used for pre-operative risk stratification in asymptomatic patients.